Reliability of muscle function and sensory perception measurements of the wrist extensors - Khamwong P. (2014)
This study determined the reliability of muscle function and sensory perception measures of the wrist extensors. The test-retest reliability of the measurements was determined by an intraclass correlation coefficient (ICC), coefficient of variation (CV), standard error of measurements (SEMs), and one-way repeated measures ANOVA using the values collected from 25 young (20.6±1.3 years) healthy male volunteers on two occasions separated by 1 day. The measures consisted of grip strength, wrist extension strength (WES), range of motion in active and passive wrist flexion and extension, choice reaction time (CRT), vibration sense (VIB), joint position error sense (JPE), cold pain (CP) and heat pain threshold, and pressure pain threshold. An acceptable reliability was determined as the ICC values greater than 0.85, CV less than 15%, and SEMs less than 5%. ICC of all measures except for JPE were greater than 0.85, only CV of JPE, CP, and VIB exceeded 15%, SEMs were higher than 5% only for JPE and CP, and the ANOVA showed a significant time effect for CRT and WES. It is concluded that most of the measurements except JPE are reliable and can be used to investigate effects of a physiotherapy intervention on the wrist extensors. © 2010 Informa UK Ltd.